The lottery - Goobie, Beth 1959- (Victoria, BC ; Custer, WA Orca Book Publishers, 2002)
When troubled, fifteen-year-old Sally wins the annual Shadow Council's lottery at her high school, she finds her ostracism by the rest of the student body difficult to bear
1
NEW, LITERATURE
Keywords: Bullying -- Fiction; Cliques (Sociology) -- Fiction; Emotional problems -- Fiction; High Schools -- Fiction; Lotteries -- Fiction; Schools -- Fiction; Canada -- Fiction